Methodology of Precision Financial and Production Management of Balanced Development of Industrial Corporations - ALEXEY N. Bogatko (Учёт. Анализ. Аудит)
The article describes a methodology of precision financial and production management of balanced development of industrial corporations and its practical applications. The methodology is based on the concept of enterprise equilibrium developed by Nobel Prize laureate John R. Hicks. This concept makes a foundation of industrial corporate management in Western countries. The methodology ensures the efficient management of financial and industrial growth of industrial corporations. The concept of enterprise equilibrium is based on a model of a balanced enterprise development. This model provides the logic for optimal formation of financial and industrial ratios of an enterprise, i. e. ratios between such parameters as: • expenses, revenue and profits, as well as investment; • capacity, performance, and output. The model together with the methodology based on it makes it possible to achieve the optimal, firstly the leading rates of financial and industrial growth. In particular it ensures the maximization of capital of industrial corporations.